Stereotip Islam dalam Film Hollywood Era 1960-an sampai 2020-an - Mustakharoh, Fajriatul; Mustain, Mustain; Hidayatullah, Ahmad (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
History records that the contestation between the West and Islam has been occurring for a long time, particularly during the Crusades, which lasted for three centuries (11th–13th centuries). Over time, these interactions gave rise to various stereotypes, especially about Islam, including within the narratives of Hollywood’s film industry. Using a qualitative research method with a critical discourse analysis approach, combined with the theory of social construction, this study seeks to explore how stereotypes of Islam have been narrated through Hollywood films from the 1960s to the 2020s. The findings of this study conclude that the representation of muslims in the Western film industry is often portrayed with a biased image, associating Islam with terrorism, violence, and fanaticism. These stereotypes emerge as a result of the long history of tensions between the Western world and the Islamic world, reinforced by political interests and media influence in shaping public opinion. The seven film samples—each from different decades—presented in this study illustrate how muslim characters are depicted as threats, ultimately reinforcing negative prejudices against Islam in global society for nearly the past century.